2024
DOI: 10.1186/s13054-024-04842-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of post-operative delirium using an overnight infusion of dexmedetomidine in patients undergoing cardiac surgery: a pragmatic, randomized, double-blind, placebo-controlled trial

Olivier Huet,
Thomas Gargadennec,
Jean-Ferréol Oilleau
et al.

Abstract: Background After cardiac surgery, post-operative delirium (PoD) is acknowledged to have a significant negative impact on patient outcome. To date, there is no valuable and specific treatment for PoD. Critically ill patients often suffer from poor sleep condition. There is an association between delirium and sleep quality after cardiac surgery. This study aimed to establish whether promoting sleep using an overnight infusion of dexmedetomidine reduces the incidence of delirium after cardiac surg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
0
2
0
2
Order By: Relevance
“… 21 Overall, the results of clinical studies and meta-analyses have not provided strong support for the use of dexmedetomidine in preventing delirium in patients undergoing cardiac or non-cardiac surgery. 72–75 These findings emphasize the importance of medication timing in dexmedetomidine research.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“… 21 Overall, the results of clinical studies and meta-analyses have not provided strong support for the use of dexmedetomidine in preventing delirium in patients undergoing cardiac or non-cardiac surgery. 72–75 These findings emphasize the importance of medication timing in dexmedetomidine research.…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, large clinical trials such as DEXACET, DECADE, DESIRE, EXACTUM, and DIRECT trial have yielded conflicting results, demonstrating that dexmedetomidine did not reduce, and even increased, the incidence of postoperative delirium. 19 , 21 , 63 , 71 , 72 At the same time, Deiner et al 20 conducted a randomized controlled trial involving 404 elderly patients undergoing non-cardiac surgery and found that continuous perioperative and postoperative infusion of dexmedetomidine did not reduce the incidence of postoperative delirium. Likewise, dexmedetomidine did not decrease the risk of postoperative atrial arrhythmias or delirium in patients undergoing cardiac surgery.…”
Section: Discussionmentioning
confidence: 99%
“…4 O delirium pósoperatório é caracterizado por um início agudo de alterações do estado mental com desatenção flutuante, pensamento desorganizado e alteração do nível de consciência. 5 Uma metanálise foi utilizada para comparar a incidência de delirium pós-operatório entre quatro sedativos: sevoflurano, propofol, dexmedetomidina e midazolam. Huang e colaboradores relataram que a incidência de delirium pós-operatório com dexmedetomidina foi menor do que com placebo, propofol, sevoflurano e midazolam, independentemente do tempo de extubação ter sido maior que 1 ou 5 horas, ou se a cirurgia foi cardíaca ou não cardíaca.…”
Section: Resultsunclassified
“…Diminui o fluxo simpático do sistema nervoso central (SNC) de maneira dose-dependente e possui efeitos analgésicos melhor descritos como poupadores de opioides. 3 Existem alguns trabalhos associando o uso da dexmedetomidina à prevenção de delirium pós-operatório, [4][5][6][7] prolongamento no tempo da analgesia em bloqueios periféricos com redução pós-operatória do consumo de opioides, 8 melhora no período da extubação, 9 possível fator de proteção sobre a depressão pós-parto em gestantes com diagnóstico prévio de depressão no pré-natal, 10 possível impacto positivo no processo de recuperação intestinal pós-operatório, 11 medicação adequada para procedimentos cirúrgicos que requeiram colaboração do paciente. 12 Farmacocinética (Figura 1) A p ó s i n j e ç ã o i n t r a v e n o s a ( I V ) , a dexmedetomidina tem início de ação após aproximadamente 15 minutos.…”
unclassified

Dexmedetomidina: Um Fármaco Versátil da Anestesia Moderna

Jedson dos Santos Nascimento,
Joaquim Muricy Neto,
Alvaro Wenâncio Pereira e Pereira
2024
RCHSI